The Requirement of Spousal Consent for Transfer of Shares in Public Companies under Ethiopian Law: A Call for Free Transferability of Shares - Zeleke, Yihun (Bahir Dar University Journal of Law, 2023)
Due to the increasing importance of shares as means of household savings, countries with statutory matrimonial regime incorporate rules, in their family law, that regulate matters related to management and transfer of shares. Especially, countries with default rule of a community of matrimonial property require spousal consent for the transfer of common property of spouses, but they exempt such requirement for the transfer of shares in a commercial company. The position of Ethiopian laws in this regard is absurd. The practice is mixed, inconsistance and arbitrary. It also creates discord of opinion to the extent of making some companies unsure of how to act. This directs the researcher to raise the following questions: Is spousal consent a requirement to transfer shares of public companies under Ethiopian law? Should spousal consent be a requirement for such transfers? Is there a lesson Ethiopia may draw from other countries in this regard? Through analysis of these issues, the writer concludes that the position of Ethiopian law concerning the issue of spousal consent vis-Ã -vis transfer of share is ludicrous and inadequate. This article argues for a clear exemption of the requirement of spousal consent for the transfer of shares in public companies and recommends the country to draw lessons from other countries to realize the free transferability of shares.